Acceptability of electronic nicotine delivery systems (ENDS) among HIV positive smokers - Yingst, Jessica (AIDS Care, 2019)
Electronic nicotine delivery systems (ENDS) have the potential to help smokers living with HIV/AIDS (PLWHA) to reduce harms from tobacco use. However, little is known about ENDS use among people living with HIV/AIDS. This study’s aim was to evaluate the acceptability of two types of ENDS among PLWHA not planning to quit smoking. The study utilized a cross-over design where participants used two ENDS in a random order, a cigalike and a button-operated device, as smoking substitutes during two use periods separated by 7 days. Exhaled carbon monoxide (CO) was analyzed and participants reported daily cigarette and ENDS use and completed subjective ratings on ENDS acceptability. Paired t-tests were used to evaluate within-subject differences in CO, cigarettes per day (CPD), and subjective ratings from baseline to follow-up for each use period. Independent t-tests evaluated differences between ENDS devices. Participants (n=17) were a mean age of 49.1 years (SD=8.8), were 53% white, and 59% male. All participants had undetectable HIV RNA viral loads and their mean CD4 count was 765.1 cells/mm(3) (SD=281.6). Participants smoked a mean of 16.9 (SD=7.9) CPD at baseline. Overall, CPD significantly decreased during both ENDS use periods (p<.01) but there were no differences in reduction between the different devices (48% cigalike v. 55% button-operated reduction, p=.44). CO decreased from baseline to follow-up only during the button-activated ENDS use period (p=.03), but there were no differences between ENDS devices. There were no significant differences in subjective ratings of acceptability between ENDS devices. These results suggest that ENDS could be a harm reduction tool for smokers with HIV.